Pengaruh Biaya Bahan Baku Terhadap Volume Produksi Pada Cv. Shaniqua Marigold Bamboo Di Rangkasbitung - Maesaroh Maesaroh; Furniawan Furniawan; Tyta Agustiara (E-Journal Studia Manajemen, 2021)
Companies that produce goods or services, the goal is to meet the needs and desires of the community. Companies certainly need raw material costs so that they can carry out the production process and create a product. So the company must set a budget for costs to be issued as working capital, especially raw material costs. Without raw materials, the production process cannot run so that it cannot produce a product. So with this the authors carry out research on the problem of the effect of raw material costs on production volume at Cv. Shaniqua Marigold Bambo in Rangkasbitung. The purpose of this study was to determine how much raw material costs incurred by the company, to find out how much volume was produced by the company and most importantly to find out how far the relationship between raw material costs and production volume at Cv. Shaniqua Marigold Bamboo in Rangkasbitung. The methodology used in this research is a quantitative method, to provide an overview of what is happening in the field by collecting data, presenting data and analyzing data. The population used is data on raw material costs and production volume in Cv. Shaniqua Marigold Bmbo. The sampling technique used was non-probability sampling, namely purposive sampling (decision method). And the analysis technique used is the Correlation Test (R), the Coefficient of Determination ( , the Simple Linear Regression Test, the T Test. To find out the relationship between the cost of raw materials of the volume of production, using the correlation Test (R) analysis, it shows that there is a relationship between the twp variables with the result of r = 0.727 with a strong interval, then the Determination Coefficient Test ( to find out how much influence the variable has. X on variable Y from the calculation results show 59.3% while the remaining 40.7% is influenced bby other factors, then the Simple Linear Regression Test is to provide an overview of variable X to variable Y, so the results Y = 1701.549 + 0.375. and finally the T test has a significant influence between the two variable with the results of tcount 3,744 > 2,001. In conclusion, raw material costs are the costs incurred by the company to buy raw materials to be used, while production volume is the amount of goods that have been produced in the company through a series of production processes.